68Ga-PSMA Uptake in Combined Hepatocellular Cholangiocarcinoma With Skeletal Metastases. (October 2017) - Alipour, Ramin; Gupta, Sandeep; Trethewey, Scott
Abstract : Abstract: 68 Ga-PSMA PET is a rapidly evolving imaging modality for whole-body staging of prostate cancer. We report a case of a 70-year-old man with mildly elevated prostate-specific antigen (8.1 μg/L) and clinical suspicion of prostate cancer (osteoblastic metastases on radionuclide bone scan) who was referred for 68 Ga-PSMA PET/CT for primary staging. Multiple 68 Ga-PSMA–avid skeletal foci, mostly associated with lytic changes on low-dose CT, as well as hepatic foci of avid 68 Ga-PSMA uptake, were identified. No abnormal focus of avid 68 Ga-PSMA uptake was identified in the prostate. On histopathological examination, the liver lesion proved to be combined hepatocellular cholangiocarcinoma.